Maintaining Product Quality, Brand Image and Increasing Usage Motives as an Effort to Increase Nivea Cosmetic's Sales - Lima, Ana (2025)
The purpose of the article is to analyze the effect of some variables on the purchase intention of cosmetic products - Nivea, such as the quality of cosmetic products, the motives for using cosmetics, and the cosmetic brand image. The population of this study is consumers of Nivea cosmetics, in the Special Region of Yogyakarta (Indonesia) with a sample of 228 respondents. The sampling method used in this study was non-random. As a result, the sample may not fully represent the broader population, which could limit the generalizability of the findings. Data was collected using a structured questionnaire, designed to gather relevant information from the participants.  The analysis was carried out using Amos, a specialized SEM software that enables the creation of path diagrams and the estimation of model parameters. The results showed that product quality had an effect on the motive for using Nivea cosmetics, product quality affected the intention to purchase Nivea cosmetics, the brand image had a significant positive effect on the motive for using Nivea cosmetics and brand image had no significant effect on purchase intentions for Nivea cosmetics. The results also show that the usage motives had a significant positive effect on the intention to purchase Nivea cosmetics in Yogyakarta, Indonesia. This work is limited to a unique cosmetic brand and the sample is concerned with a specific region of Indonesia. This work brings attention to the cosmetic industry, the implications to brand image, and the effects on purchase intentions for Nivea Cosmetics. DOI: https://doi.org/10.54663/2182-9306.2024.v.12.n.49-67